If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2x + 1) + -1(x + 1) = 5x + -16 Reorder the terms: 2(1 + 2x) + -1(x + 1) = 5x + -16 (1 * 2 + 2x * 2) + -1(x + 1) = 5x + -16 (2 + 4x) + -1(x + 1) = 5x + -16 Reorder the terms: 2 + 4x + -1(1 + x) = 5x + -16 2 + 4x + (1 * -1 + x * -1) = 5x + -16 2 + 4x + (-1 + -1x) = 5x + -16 Reorder the terms: 2 + -1 + 4x + -1x = 5x + -16 Combine like terms: 2 + -1 = 1 1 + 4x + -1x = 5x + -16 Combine like terms: 4x + -1x = 3x 1 + 3x = 5x + -16 Reorder the terms: 1 + 3x = -16 + 5x Solving 1 + 3x = -16 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 1 + 3x + -5x = -16 + 5x + -5x Combine like terms: 3x + -5x = -2x 1 + -2x = -16 + 5x + -5x Combine like terms: 5x + -5x = 0 1 + -2x = -16 + 0 1 + -2x = -16 Add '-1' to each side of the equation. 1 + -1 + -2x = -16 + -1 Combine like terms: 1 + -1 = 0 0 + -2x = -16 + -1 -2x = -16 + -1 Combine like terms: -16 + -1 = -17 -2x = -17 Divide each side by '-2'. x = 8.5 Simplifying x = 8.5
| -70+-35x=-245 | | solvew^2-2w+1=0 | | 3*2=-2(-5)-4 | | 5*2=3(-5)+20 | | 3x-12-5x-10= | | 36+6X=34-4X | | -4=6x+7x+9 | | 8*(2p-4)*3p=20 | | 6x+1+5x=-65 | | a+10=b+2 | | 1+2x=x-2-4x | | -2x-5y=-27 | | 14(d+30)=-196 | | -4+4x-5x=-14 | | 3f=(2f+8) | | 6X-12+4X-1=-X+12-3X+5 | | x+(x+10)+2x=98 | | 4x+3=x+x+29 | | 2t-1=2t-5 | | 4y+3=y+21 | | 4y+3=y+22 | | 625-25x=0 | | (35x+67y)+(-20x+41y)= | | f(x-1)=x^2+3 | | f(x-1)=x^2-3 | | 14d+30=196 | | 14z=3(4z+3) | | 10x^3-11x^2-6x=0 | | 2x-1+3=4 | | 32=-0.8m | | -3.2x=14.4 | | -1.25+.25x=0 |